Psychological conditions, social coexistence and rehabilitation of ex-prisoners under Internal Security Act in the southern border provinces of Thailand - Ruangying, Jiraporn; Kunsuya, Ajcharapun; Suwanwong, Danuwat (Humanities, Arts and Social Sciences Studies, 2024)
Ex-prisoners are defined as those under the Internal Security Act who have previously committed offenses connected to the incidences of disturbance/conflicts in Thailand's southern border provinces. Additionally, certain people have a strong propensity for repeat transgressions, which could be detrimental to society. This study used qualitative research techniques and in-depth interviews to examine psychological circumstances, social coexistence, means of subsistence, occupations, and current support practices. Following a period of reintegration into society, some observations were made namely: i) 23 ex-prisoners in the southern border provinces were on insurgent charges, ii) 10 government employees with five years of experience were in care, assistance, healing, and rehabilitation process, and iii) four members of civil society with five years of experience in aid, recovery, and rehabilitation were among the informers for the sources of information. The results also revealed that most ex-prisoners experienced psychological stress and anxiety after re-entering society. This phenomenon occurs due to issues related to debt, low income, localized violence, and frequent visits by the army troops' to their houses, it was discovered that some groups were stigmatized by local residents. Nevertheless, they were found to have adjusted to living and got along well with their families. In terms of occupation and sources of income, it was found that most were merchants, general laborers, and rubber tappers. Additionally, the community networks supporting the restoration of coexistence in the community are either the responsibility from government agencies or authority both direct or indirect involvement of the civil society organizations/Non-Governmental Organisation (NGOs). The findings of this study will be helpful in establishing a framework for assisting and rehabilitating the quality of life of ex-prisoners under the Internal Security Act that is congruent with the local requirements and context.